A better approach for left ventricular training in transposition of the great arteries and intact interventricular septum: Bidirectional cavopulmonary anastomosis and pulmonary artery banding. (25th January 2019) - Bilal, Mehmet Salih; Özyüksel, Arda; Kemal Avşar, Mustafa; Demiroluk, Şener; Küçükosmanoğlu, Osman; Yalçın, Yalım
Abstract: Objective: Management of the patients with transposition of the great arteries and intact ventricular septum may be challenging beyond the newborn period. Herein, we would like to present our alternative strategy for training the left ventricle in these patients. Methods: Six patients with transposition of the great arteries and intact ventricular septum were evaluated in our clinic. Two of them were palliated with Glenn procedure and pulmonary banding as a definitive treatment strategy at other centers. Four patients were operated on and a bidirectional cavopulmonary anastomosis in combination with pulmonary artery banding was performed (stage‐1: palliation and ventricular training) in our center. In four out of these six patients, arterial switch operation was performed with takedown and direct re‐anastomosis of the superior vena cava to right atrium after an interstage period of 21‐30 months (stage‐2: anatomical repair). Results: Any mortality was not encountered. The left ventricular mass indices increased from 18‐32 to 44‐74 g/m 2 in patients undergoing the anatomical repair. All of the patients were uneventfully discharged following the second stage. The mean follow‐up period was 20 months (9‐32 months) following stage 2. All of the patients are doing well with trivial neoaortic regurgitation and normal biventricular function. Conclusions: Bidirectional cavopulmonary anastomosis with pulmonary artery banding may be a promising left ventricle training approach in ventriculoarterial discordance when compared to the traditional pulmonary artery banding with concomitant systemic‐to‐pulmonary artery shunt procedures which still carry a significant interstage morbidity and mortality.